PENGARUH FASILITAS BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X PROGRAM KEAHLIAN AKUNTANSI DI SMK KANSAI PEKANBARU - Embuni Dewi; Rina Selva Johan; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This study aims to determine whether there is influence between learning facility to the learning outcomes of students in vocational Kansai Pekanbaru with 30 sample and sampling technique using sampling techniques Saturated (census). Data analysis techniques used in this study is a simple linear regression analysis. The research showed that the students' learning facilities are in adequate category. It is known from respondents (students) that is equal to 63.3% of students stated adequate and student learning outcomes that are in both categories with category value of students who dominate the value of B+. The learning facilities simultaneously affect the students' learning outcomes by 0635. The next simple linear regression equation Y = 2.400 + 0.023. so if the variable learning facilities increased by 1%, the result of learning will increase sebessar 0023. Meanwhile, the coefficient of determination obtained from variable learning facilities amounted to 63.5% and the remaining 36.5% influenced by other variables that are not addressed in this study.Keywords : Learning Facilities and Student Results